A macrophage-activating, injectable hydrogel to sequester endogenous growth factors for in situ angiogenesis. (July 2017) - Feng, Yanxian; Li, Qiu; Wu, Dang; Niu, Yiming; Yang, Cheng; Dong, Lei; Wang, Chunming
Abstract: Biomaterials scaffolds designed for many regenerative applications are expected to support neo-vascularisation, which is now being hampered by two limitations – the instability of exogenous growth factors (GFs) that are delivered to promote angiogenesis; and the loss of extracellular matrix components that bind and stabilise GFs. Here, we report the design and evaluation of an injectable hydrogel system aimed at restoring a GF-binding microenvironment to enhance the pro-angiogenic functions of endogenous GFs. This gel comprises two polysaccharides with their unique bioactivities: Konjac glucomannan (KGM) as the building block of the gel scaffold, for its demonstrated capacity to activate macrophages/monocytes to secrete pro-angiogenic/-mitogenic GFs; and heparin (Hep), a representative glycosaminoglycan molecule that binds numerous pro-angiogenic GFs, as functional moieties to sequester the macrophage-produced GFs. Modified with tyramine (TA) groups, the two polysaccharides can be co-polymerised and rapidly form into hydrogel upon enzyme catalysis. The designed KGM-TA/Hep-TA hydrogel successfully preserves the macrophage-activating function and GF-binding affinity of the two components, respectively, and, once subcutaneously implanted, effectively sequestered the locally-produced GFs in situ and promote the formation and maturation of blood vessels in mice. In summary, the designed hydrogel system demonstrates a feasible approach to stimulate the production and harness the function of endogenous GFs for inducing blood vessel formation in vivo, without the addition of any exogenous proteins. This design may provide an innovative, open platform to promote vascularisation for various regenerative purposes.